2008 First International Conference on Intelligent Networks and Intelligent Systems 2008
DOI: 10.1109/icinis.2008.30
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Wireless Sensor Networks to In-Service Motor Monitoring and Energy Management

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Hu [34,35] presents a DSP-based system for motor monitoring using the air-gap torque method and WSN for data transmission. The estimation of various parameters such as power factor, efficiency, speed, and torque was proposed.…”
Section: Motor Monitoring Systemsmentioning
confidence: 99%
“…Hu [34,35] presents a DSP-based system for motor monitoring using the air-gap torque method and WSN for data transmission. The estimation of various parameters such as power factor, efficiency, speed, and torque was proposed.…”
Section: Motor Monitoring Systemsmentioning
confidence: 99%
“…In recent decade, Wireles Sensor Networks (WSNs) have been improved and applied popularly in many fields because of low cost, low power consumption, small size and short transmission distance [1][2][3][4]. Hence, the ZigBee standard has been proposed to satisfy these requirements to achieve the goal of longer lifetime with higher reliability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of these application like robotic navigation Fu et al (2009), aircraft corrosion monitoring Demo et al (2010) , direct load control in residential areas Molina-Garcia et al (2007), personal mobile physiological monitoring and management system for chronic disease Toh et al (2008), Wildfire detection Antoine-Santoni et al (2006), www.intechopen.com in-service motor monitoring and energy management Hu (2008), application in petrochemical industry Ke et al (2008), application for critical infrastructure risk analysis of fossil fuelled power stations Isreb (2006) and tactical military applications Lee et al (2009) can be found in the litrature.…”
Section: Wireless Sensor Network Applicationsmentioning
confidence: 99%